1998
DOI: 10.1007/s001980050090
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Activity and Fractures on Ultrasound Parameters in Elderly People

Abstract: Abstract. In this cross-sectional study we investigated the relationship between ultrasound measurements in the calcaneus versus daily physical activity and fractures sustained in the past in elderly subjects. Ultrasound measurements were performed at both heels, which enabled us to examine determinants of differences between contralateral heels. Participants were 132 men and 578 women, aged 70 years and over (mean age and standard deviation (SD): 83 ± 6 years), living in homes for the elderly (n = 343) or apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Another potential limitation is the fact that we did not investigate potential differences in physical activity between the fractured and the control group. Since SOS, BUA and BMD have been reported to be positively related to physical activity [58][59][60], any differences in physical activity between the groups will bias the discrimination. However, this should affect all the devices equally.…”
Section: Discussionmentioning
confidence: 96%
“…Another potential limitation is the fact that we did not investigate potential differences in physical activity between the fractured and the control group. Since SOS, BUA and BMD have been reported to be positively related to physical activity [58][59][60], any differences in physical activity between the groups will bias the discrimination. However, this should affect all the devices equally.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are generally consistent with observations made by other epidemiological studies among women of different ethnicities, using complex PA assessment tools as well. These studies mainly observed a positive association between PA and BUA levels [ 4 , 23 , 24 , 27 ], only Brahm et al and Brunner et al noticed no association [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that lack of physical activity is a risk factor for decline in bone mass [1], falls and hip fractures [2][3][4][5], and cardiovascular mortality [6] in older people. Within the Longitudinal Aging Study Amsterdam (LASA), physical activity was an important determinant for falls and fractures [7], and was negatively associated with abdominal fat [8].…”
Section: Introductionmentioning
confidence: 99%